Pengaruh Kualitas Aset, Likuiditas, Rentabilitas dan Efesiensi Operasional terhadap Kecukupan Modal - Neneng Uswatun Hasanah; Gusganda Suria Manda (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
This study aims to understand and determine the effect of asset quality, liquidity, profitability, and operational efficiency on the adequacy of private banks listed on the Indonesia Stock Exchange in 2015-2020. The method used is the classic assumption test: normality test, multicollinearity test, heteroscedasticity test, durbin witson autocorrelation test, hypothesis testing: t test and f test, and multiple linear regression analysis, analysis of the coefficient of determination assisted by the SPSS 16 program. Types of data used that is secondary with quantitative data in the form of annual financial data of banking companies. The population in this study were 39 private banking companies, with the selected sample being 5 banking companies with the 2015-2020 period listed on the Indonesia Stock Exchange. The technique used is purposive sampling. Based on the results of the hypothesis, it shows that the variables of asset quality, liquidity, profitability and operational efficiency have no partial effect on the capital adequacy variable, while simultaneously there is a significant influence between the variables of asset quality, liquidity, profitability and operational efficiency on the capital adequacy variable, with a simultaneous level of influence. of 49.9%, while the rest can be influenced by other variables or factors not included in this study